Critically Analyzing the Social Media Images Portraying Imran Khan as an Alternate of Jinnah - Attiya Khanam; Sarwat Jabeen (Corresponding Author); Rashida Ahmad; Fatima Farooq (Al-Qanṭara, 2024)
This paper claims that the study of political images and efforts of politicians and their supporters to create the public image of politicians is moving towards more interdisciplinary endeavors. In this respect, our purpose is to investigate the changing patterns of political communication, by briefly showing the discursive features of unique Jinnah- Imran images. The paper analyzes the unique discursive strategy to portray the positive image of the politicians by creating an emotional cue. This research paper presents the concepts of political impression management and perception politics and discusses that perception politics which actually is the modernization of politics can be perceived as a trend toward commercialization, globalization, and a visual culture in which mass media and social media in particular play an important role. The researchers have used the methodology of critical discourse analysis and uncover the discursive features of the unique Jinnah- Imran political images. They conclude that such dramatic discursive strategies are used to create the desired images of politicians by making people emotional and these strategies have nothing to do with any logical elements.